Metallothionein gene expression and protein levels in triploid and diploid oysters Crassostrea gigas after exposure to cadmium and zinc. - Marie, Véronique; Gonzalez, Patrice; Baudrimont, Magalie; Boutet, Isabelle; Moraga, Dario; Bourdineaud, Jean-Paul; Boudou, Alain (Environmental Toxicology and Chemistry, 2006)
International audience Quantitative real-time polymerase chain reaction (PCR) was used to compare for the first time the differential expression of metallothionein (MT) isoform genes, together with biosynthesis of the total MT proteins, in the gills of triploid and diploid juvenile Pacific oyster Crassostrea gigas in response to cadmium (Cd) and zinc (Zn) exposure. Oysters were exposed to Cd (0.133 mM), Zn (15.3 mM), and Cd1Zn for 14 d. Results showed similar response capacities to metal exposures in the two populations. No significant difference was revealed in terms of MT gene expression, MT protein synthesis, and Cd accumulation. However, triploid oysters bioaccumulated Zn 30% less efficiently than diploid oysters. Among the three MT isoform genes, CgMT2 appeared to be more expressed than CgMT1, whereas CgMT3 appeared to be anecdotal (106 times lower than CgMT2). CgMT2 and CgMT1 gene expression levels were increased sevenfold in the presence of Cd, whereas Zn appeared to have no effect. A twofold increase in MT protein levels occurred in response to Cd exposure. Discrepancies between mRNA and protein levels suggest that in C. gigas MT are regulated at the transcriptional level, as well as at the translational level.